Determinants of farmer's participation in off-farm employment: A case study in Kedah Darul Aman, Malaysia - Abdul Hakim, Roslan; Siti Hadijah, Che Mat (Asian Economic and Social Society, 2011)
This paper investigates the determinants of agricultural households’ participation in off-farm employment. Towards this end, a logit model is employed to identify factors that determine the participation in off-farm employment. Here, determinants of participation in off-farm employment are divided into four categories – individual, household, farm and local area characteristics.With regards to the local area characteristics, the analysis is extended by including a new variable, which is the economic characteristic of the area.The results of the analysis show that the main determinants that influence the farmer’s decision to participate in off-farm employment are age,gender, household size, dependency ratio, remittance, land size, types of agricultural activities, working hours allocated to the farm, the ratio of income from agricultural sources in total income of the farmer. Furthermore, this study uncovers that the economic characteristic of the area where the farmer reside is important determinant of the farmer’s decision to participate in off-farm job.One of the policy implications from the finding of this study is that, if the agricultural households are to be encouraged to participate in off-farm jobs, a balanced development in the rural areas must be pursued.